Cross-cultural examination of social support, academic support, and well-being: A comparative study of Indian and international students - Beri, Nimisha; Thakur, Kanika; Kumar, Narendra (Journal of International Students, 2025)
In this study, we used a comprehensive survey instrument to examine the nexus of social support, academic assistance, and well-being among 190 university students, including 64 international and 126 Indian students, with gender parity. It addresses a critical gap in the literature by exploring how emotional and educational support intertwine and elucidating their impact on students’ psychological states. The findings highlighted a positive correlation between social and academic support and overall well-being for both cohorts, with minor cultural differences. The study underscores the importance of culturally sensitive interventions in fostering student well-being, calling for tailored support systems. These insights can enhance support services in academic institutions for diverse student populations with the aim of enhancing their holistic well-being.